2012
DOI: 10.1111/j.1440-1789.2012.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of circumventricular organs and third ventricle ependyma in the rat: potential markers for periventricular tumors

Abstract: Circumventricular organs (CVOs) are specialized ventricular structures around the third and fourth ventricles of the brain. In humans, these structures are present during the fetal period and some become vestigial after birth. Some of these organs, such as the pineal gland (PG), subcommissural organ (SCO), and organum vasculosum of the lamina terminalis, might be the sites of origin of periventricular tumors, notably pineal parenchymal tumors, papillary tumor of the pineal region and chordoid glioma. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Tight junctions are located at the apical pole of the ependymal cells with the typical honeycomb pattern. Our study supports the view that the SCO is sequestered within a double‐barrier system (Rodriguez et al, ) and supplements the work of Szathmari et al (), who demonstrated claudin 3 immunoreactivity in ependymal cells of the SCO. Importantly, in contrast with the ependymal cells of other CVOs, ependymal cells in the SCO display numerous cilia that coat the ventricular wall and project into the ventricular lumen (Meiniel, ).…”
Section: Discussionsupporting
confidence: 92%
“…Tight junctions are located at the apical pole of the ependymal cells with the typical honeycomb pattern. Our study supports the view that the SCO is sequestered within a double‐barrier system (Rodriguez et al, ) and supplements the work of Szathmari et al (), who demonstrated claudin 3 immunoreactivity in ependymal cells of the SCO. Importantly, in contrast with the ependymal cells of other CVOs, ependymal cells in the SCO display numerous cilia that coat the ventricular wall and project into the ventricular lumen (Meiniel, ).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding if confirmed by others, may suggest a potential role of this transcription factor in the development of morphologically heterogeneous neoplasms in the third ventricular region. As recently reported [8] the exact role of TTF-1 and other potential markers in the histogenesis of sellar tumours should be further explored with molecular techniques. This should contribute to a better understanding of new tumour signalling pathways involved in these tumours and will hopefully lead to the development of targeted therapy with specific inhibitors.…”
Section: To the Editormentioning
confidence: 96%
“…There is some evidence that TTF-1 may contribute to the control of sexual maturation through activation of ErbB2, a membrane bound molecule with tyrosine kinase activity belonging to the Epithelial Growth Factor Receptor (EGFR) family [7]. Interestingly ErbB2 expression was reported recently using microarray technique in third ventricle ependyma in the rat [8]. TTF-1 is used in pathology as a diagnostic marker for the identification of metastatic lesions of thyroid and bronchial origin.…”
Section: To the Editormentioning
confidence: 99%
“…In these regions, the BBB capillaries are highly fenestrated with less tight junctions between endothelial cells creating a more permeable barrier (Bennett et al, 2009). Seven periventricular regions display differential barrier properties and are collectively known as the circumventricular organs: i, sub-fornical organ; ii, organum vasculosum of the lamina terminalis; iii, pituitary; iv, area postrema; v, median eminence (ME); vi, subcomissural organ; and vii, pineal (Bennett et al, 2009; Szathmari et al, 2013). In these regions, in addition to the cells that classically form the BBB vessels, a differential type of radial glial cell, termed tanycytes are also found in the interface between the spinal fluid and the capillaries (Rodríguez et al, 2010).…”
Section: Bbb In the Hypothalamic Areamentioning
confidence: 99%